APPLICATION OF SWOT AND ANP METHODS IN ORDER TO SELECT THE AGROINDUSTRIAL DEVELOPMENT STRATEGY BASED ON TAPAI IN BONDOWOSO - Elok Kurnia Novitasari; Didiek Hermanuadi; Aulia Brilliantina (University of Sultan Ageng Tirtayasa, 2020)
Tapai is one of the products that become the flagship and image of Bondowoso district. So, the existence of cassava is very supportive to the continuity agroindustry based on Tapai. The main purpose of this research is determining methods that can be used to select the agro-industrial development strategies. One of the decision-making methods that can be used for the selection of agro-industrial development strategies is the Analytic Network Process (ANP) method. In the formulation of strategies is also used SWOT analysis. Based on the research, a priority strategy is obtained, namely the WO strategy, namely strengthening capital for the Tapai agroindustry business and increasing promotion by conducting training.